GROWING THE CHARACTER OF RESPONSIBILITY THROUGH EXTRA TAPAK SUCI PUTERA MUHAMMADIYAH AT MI MUHAMMADIYAH KARANGANYAR - Gesang Triwigati (Universitas PGRI Yogyakarta, 2022)
This study aims to describe the character of responsibility through extra Tapak Suci Putera Muhammadiyah at MI Muhammadiyah Karanganyar. The character in this study is focused on the character of responsibility. Cultivating the character of responsibility starting from planning, implementation, to inhibiting factors and supporting factors for program implementation. The research was conducted at MI Muhammadiyah Karanganyar. This research uses descriptive qualitative research. Using direct observation data collection techniques, in-depth interviews and document studies using triangulation data validity tests, both triangulation of data sources and triangulation of data collection techniques. The data analysis technique uses the Miles Huberman interactive analysis model.The results of this study indicate that growing the character of responsibility through the Tapak Suci extracurricular begins with; (1) Prepare materials according to the level of students referring to the syllabus and materials of the Tapak Suci College. (2) Providing character education on the sidelines of the exercise according to the material provided. (3) Analyzing the character content of the Tapak Suci traditional ceremony. The implementation of character education begins with; (1) Arrange the rows of students before heading to the practice site. (2) conveying character content on the sidelines of the Tapak Suci practice. (3) assigning students who are at a higher level to be an example for students who are below their level. The inhibiting factors in growing the character of responsibility through the Tapak Suci extracurricular are; (1) limited human resources who can train Tapak Suci with character education content. (2) short extracurricular implementation time. The supporting factors are; (1) being taught by a Tapak Suci trainer with a Young Cadre level who understands the science of Tapak Suci and the values of the noble character of Pencak Silat. (2) support for good facilities and infrastructure.